An epistemological inquiry into the sociology of the uses of information and communication technologies - سوهيلة زوار (International Journal of Social Communication, 2018)
The information and communication technologies have penetrated into the cultural and moral fabric of our societies. They reflect now a social and cultural practice and they are not only considered as Technical tools but also don’t reveal their significance through the researcher‘s perception away from the user’s view. A trend which is in line with the approach of “Sociology of uses” which liberates the searcher of the obsession of the technology and pushed him to look into the communication phenomena based on a network of theoretical concepts which is able to approach the appropriations of the technology with the communication process within a given society (social uses) .therefore , we will try to answer a fundamental question which discuss the effectiveness of this new approach in examining the communication phenomena by subjecting them to an epistemological question